Geldpolitik bei Unsicherheit (Monetary Policy Under Uncertainty) - Heinz-Peter Spahn (Intervention. Zeitschrift fuer Ökonomie / Journal of Economics, 2007)
– "Uncertainty" indicated a critical post Keynesian argument against neoclassical monetarism, but was taken up by the European Central Bank (ECB) in order to emphasize the importance of the money supply indicator in its "two pillar" strategy. In a state of model uncertainty on behalf of market and policy agents, the quantity of money is meant to control long-term inflation expectations. However, the instability of money demand and the intention to reject the responsibility for the cycle leads the ECB to modify the quantity theory towards a credit theory of nominal income. The ECB decides on the validity of the money-inflation nexus in a discretionary way and thus undermines the credibility of the monetary pillar. Lack of information is also offered in order to defend the ECB's single price-stability target. Following only this target is suboptimal on welfare-theoretic grounds as the ECB indirectly accepts the non-neutrality of money.
Keywords: E12; E41; E58; 330; interest rate policy; new Keynesian model; money demand; two pillars; inflation expectation